Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menerapkan Kombinasi Metode Simple Additive Weighting (SAW) dengan Rank Order Centroid (ROC) - Muliati Badaruddin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
This research discusses the combination of Rank Order Centroid (ROC) and Simple Additive Weighting (SAW) methods to produce company manager's decisions in evaluating employee performance. The results of employee performance appraisal are expected to be more effective and objective due to the support of the decision support system used. Many studies have been conducted in performance appraisal using the Simple Additive Weighting method, but have not or do not use good weighting. With a combination of weighting and ranking methods, the outcome of the decision will certainly be more effective.